Fluid dynamic and heat transfer processes between solid surfaces and non-Newtonian liquid droplets. (5th September 2015) - Moita, A.S.; Herrmann, D.; Moreira, A.L.N.
Abstract: This paper addresses the experimental and theoretical description of the fluid dynamic and thermal behaviour of non-Newtonian (shear-thinning) droplets impacting onto smooth and micro-patterned heated surfaces. The shear-thinning liquids are mixtures of water + xanthan gum prepared with different concentrations of the gum, namely 0.05%, 0.10%, 0.15% and 0.35%wt. For droplet impacts over the surfaces heated bellow the boiling temperature of the liquid, the shear-thinning effect is clearly governed by the concentration of the non-Newtonian component, which is associated to the consistency coefficient of the constitutive model describing the viscous behaviour of the flow. In line with this, models predicting the spreading of Newtonian droplets are revisited and an alternative one is proposed, which integrates the non-Newtonian behaviour. The results suggest that heating the surface (and consequently the liquid) alters the rheology of the non-Newtonian mixture and reverses the increase of the zero viscosity, which is observed for impacts onto non-heated surfaces, thus allowing a larger spreading diameter and a significant recoiling phase for droplets with high concentrations of the non-Newtonian component. The heat transferred at droplet–surface interaction, during the spreading of the droplet is also evaluated. The analysis evidences the strong coupling between the heat transfer process and the spreading dynamics, for the non-Newtonian droplets. Further heating the surface above the boiling temperature of the liquid, the droplets impact the surfaces within the nucleate boiling regime and thermal induced atomization occurs. In this case, Phase Doppler measurements are taken to characterize the size of the secondary droplets generated within this process. The results show that the thermal induced atomization is mainly triggered by the force balance between surface tension and vapour pressure forces, so the viscosity plays a secondary role. Highlights: Dynamics and heat transfer are described for the impact of shear-thinning droplets. Without boiling, the shear-thinning effect is governed by the gum concentration. An alternative model to predict the spreading diameter is proposed. Thermal induced atomization is weakly dependent on the non-Newtonian viscosity.